Cui prodest libraries authority work? - Simona Turbanti (JLIS.it, 2014)
Eleven years ago, in Florence, during an international conference on authority control, many experts reflected on this important aspect of cataloguing. This paper looks at the current state of authority work and try to conceive some cues to reshape authority control. Libraries can afford this costly process only in cooperation with other partners, especially cultural and research institutions but also publishers, local governments and other interested subjects. Two examples of successful partnership are the Social Networks and Archival Context Project and the well-known Virtual International Authority File. An opportunity for libraries could be also to extend authority control to wide bibliographic databases that abound with homonymies